The Impact of Skills and Personality on Employee Work Productivity: Case Study from PT. Sumber Permata Mineral, North Morowali Site, Indonesia - Ulfa, Aulia; Dahri, Nur Wahyunianti; Puspita, Retno Ayu (Manunggal Halim Jaya, 2024)
This study examined the effect of skill and personality on employee productivity at PT Sumber Permata Mineral Site North Morowali. The research uses a quantitative approach, with a sample selected through non-probability sampling techniques involving 76 respondents. Data was collected through observation, interviews, and the distribution of questionnaires directly to the respondents. The quality of the research instruments was tested using validity and reliability tests. The analytical method employed is multiple linear regression analysis, followed by hypothesis testing using partial tests (t-statistical test), simultaneous tests (F-statistical test), and the coefficient of determination to determine the contribution of independent variables to the dependent variable. The results of the study indicate that (1) Skill has a significant partial effect on work productivity, (2) Personality has a partial and significant effect on work productivity, and (3) Skill and personality simultaneously have a significant effect on work productivity. However, the combined contribution of skill and personality to employee work productivity is relatively weak, with a percentage of 47.7%. This suggests that other factors, accounting for 52.3%, may also influence employee work productivity at PT Sumber Permata Mineral Site North Morowali.